Individualised dosimetry and safety of SIRT for intrahepatic cholangiocarcinoma - Willowson, Kathy P.; Eslick, Enid M.; Bailey, Dale L. (EJNMMI physics, 2021)
Background The aim of this study was to investigate the safety and efficacy of selective internal radiation therapy (SIRT) with 90 Y resin microspheres for the treatment of Intrahepatic Cholangiocarcinoma (ICC). A total of 23 SIRT procedures from 18 ICC subjects were analysed to determine a lesion-based dose/response relationship with absorbed dose measures from 90 Y PET and metabolic response as measured on [ 18 F]FDG PET. Average absorbed dose ( D avg ), minimum dose to 70% of the volume ( D 70 ), volume receiving at least 50 Gy ( V 50 ), biological effective dose (BED) and equivalent uniform dose (EUD), were compared to changes in metabolic volume, maximum standardised uptake value (SUV max ) and total lesion glycolysis (TLG). Dose to normal liver was assessed with changes in liver uptake rate as measured with [ 99m Tc]mebrofenin scintigraphy for a cohort of 20 subjects with primary liver malignancy (12 ICC, 8 hepatocellular carcinoma (HCC)). Results Thirty-four lesions were included in the analysis. A relationship was found between metabolic response and both D avg and EUD similar to that seen previously in metastatic colorectal cancer (mCRC), albeit trending towards a lower response plateau. Both dose and SUV coefficient of variation within the lesion (CoV dose and CoV SUV ), baseline TLG and EUD were found to be mildly significant predictors of response. No strong correlation was seen between normal liver dose and change in [ 99m Tc]mebrofenin liver uptake rate; low baseline uptake rate was not indicative of declining function following SIRT, and no subjects dropped into the ‘poor liver function’ category. Conclusions ICC lesions follow a similar dose–response trend as mCRC, however, despite high lesion doses a full metabolic response was rarely seen. The CoV of lesion dose may have a significant bearing on response, and EUD correlated more tightly with metabolic response compared to D avg . SIRT in primary liver malignancy appears safe in terms of not inducing a clinically significant decline in liver function, and poor baseline uptake rate is not predictive of a reduction in function post SIRT.